Organisational Inertia in Healthcare: An Integrative Qualitative Review Using the Dead Horse Theory - Michael Mncedisi Willie; Siyabonga Jikwana (International Journal of Research and Community Empowerment, 2026)
Organisational inertia continue to influence the effectiveness of healthcare systems globally, contributing to operational inefficiencies, increased workforce pressures, and concerns regarding the sustainability of optimal patient outcomes despite continued reform efforts. While structural interventions are frequently introduced, many fail to produce meaningful change, instead reinforcing existing dysfunctions. Using the Dead Horse Theory as an interpretive lens, this study examines how organisational inertia, leadership avoidance, and systemic denial interact to sustain ineffective practices in healthcare settings. An integrative qualitative literature review was conducted, drawing on peer-reviewed studies sourced from major academic databases. The analysis focused on how organisational inertia, leadership behaviour, workforce dynamics, ethical accountability, and stakeholder engagement interact as interconnected rather than isolated factors. Through thematic and narrative synthesis, the study identified recurring patterns of symbolic reform, leadership avoidance, workforce disengagement, and weakened organisational responsiveness across healthcare contexts. Findings indicate that organisational inertia stabilises outdated routines and limits adaptability, while leadership avoidance reinforces these patterns through symbolic or procedural actions that fail to address underlying problems. Although such approaches may maintain short-term stability, they contribute to long-term consequences including burnout, reduced motivation, weakened team cohesion, and diminished psychological safety. Ethical accountability and stakeholder engagement emerged as key moderating factors that influence whether systems remain stagnant or shift toward adaptive change. The study develops an integrated conceptual framework linking organisational inertia, leadership avoidance, workforce dynamics, ethical accountability, and stakeholder engagement into a unified explanation of healthcare system performance. The study challenges linear interpretations of healthcare reform and highlights the need for adaptive, ethically grounded, and accountable leadership to disrupt entrenched system failure, supporting Sustainable Development Goal (SDG) 3: Good Health and Well-being and Sustainable Development Goal (SDG) 8: Decent Work and Economic Growth.